Detection of sequential activation of left atrium and coronary sinus musculature in the general population. Issue 6 (1st June 2016) - Ota, Masaki; Kaneko, Yoshiaki; Nakajima, Tadashi; Irie, Tadanobu; Iijima, Takafumi; Saito, Akihiro; Kurabayashi, Masahiko
Abstract: Background: The direction of impulse propagation across the coronary sinus (CS) musculature (CSM) is an important piece of the mechanistic puzzle underlying atrial tachyarrhythmias. We hypothesized that in the general population, the sequence of left atrial (LA) to CSM electrograms recorded in the CS reflects the direction of impulse propagation over the CSM. Methods: We studied 19 patients with atrioventricular (AV) reentrant tachycardia (RT) utilizing a left‐sided accessory pathway (AP) and 21 patients with typical counterclockwise atrial flutter (AFL). Conduction through the CSM during AVRT and AFL is from the left atrial (LA) to the right atrial (RA) and from the RA to LA direction, respectively. CS recordings of retrograde conduction over the AP and of AFL were analyzed in search of far‐field, LA potentials. Results: Among 19 patients with AP, LA potentials were visible in 7 (37%), all in an LA → CSM activation sequence, while among the 21 patients with AFL, LA potentials were visible in 14 (67%), all in a CSM‐LA activation sequence ( P <0.0001). The prevalence of LA potentials was similar between both study groups ( P =0.1119), and the overall prevalence was 53%. Conclusions: Far‐field LA potentials are often recorded in the CS during sequential LA and CSM activation in the general population. The timing of LA potentials in CS recordings reflected the direction of conduction across the CSM.